1996
DOI: 10.1128/jvi.70.3.1439-1447.1996
|View full text |Cite
|
Sign up to set email alerts
|

A preferred region for recombinational patch repair in the 5' untranslated region of primer binding site-impaired murine leukemia virus vectors

Abstract: Transduction of primer binding site-impaired Akv murine leukemia virus-based retroviral vectors from the murine packaging cell lines ⌿-2 and ⍀E was studied. The efficiency of transduction of the neo marker of all mutated constructs was found to decrease by 5 to 6 orders of magnitude compared with that of the wild-type vector. Thirty-two of 60 transduced proviruses analyzed harbored a primer binding site sequence matching a glutamine tRNA primer. Sequence analysis of the regions flanking the glutamine tRNA prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
60
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 51 publications
8
60
0
Order By: Relevance
“…PBS‐mediated second‐strand transfer and completion of reverse transcription should only occur for those minus‐strand DNAs containing Lys3 PBS at their 3'end explaining the exclusive detection of Lys3 PBS in the vector DNA of transduced target cells. This would be similar to a mechanism described for the transfer of MLV‐based vectors with impaired PBS, where reverse transcription was observed to initiate on copackaged endogenous retroviral sequences 31. In our previous study, in which SIV tRNA usage was investigated, PBS‐mutated SIV was not infectious in the absence of a complementing tRNA 17.…”
Section: Discussionsupporting
confidence: 72%
“…PBS‐mediated second‐strand transfer and completion of reverse transcription should only occur for those minus‐strand DNAs containing Lys3 PBS at their 3'end explaining the exclusive detection of Lys3 PBS in the vector DNA of transduced target cells. This would be similar to a mechanism described for the transfer of MLV‐based vectors with impaired PBS, where reverse transcription was observed to initiate on copackaged endogenous retroviral sequences 31. In our previous study, in which SIV tRNA usage was investigated, PBS‐mutated SIV was not infectious in the absence of a complementing tRNA 17.…”
Section: Discussionsupporting
confidence: 72%
“…Additionally, it was shown that the frequency of RT template switching is equal during minus-and plus-strand DNA synthesis (2). Other in vivo studies have also shown that the dimer linkage structure constitutes a hot spot for intermolecular template switching events (27)(28)(29).…”
mentioning
confidence: 98%
“…The mutations were devised to give a low match to the 3Ј end of any known murine tRNA molecule (36). In accordance with previous studies on PBS alterations (10,17,20,22,30), the PBS-x2 mutations severely diminished the replication capacity of the vector due to the pivotal functions of the PBS during retroviral replication.…”
Section: Discussionmentioning
confidence: 84%
“…While genetic analysis of viral RNA and proteins has already contributed valuable information, we here present the possibility of also modifying the host-derived tRNA that plays key roles in the process. We have previously shown that PBS mutations designed not to match any naturally occurring tRNA molecule result in a strong impairment of vector transduction (20). To test the feasibility of making replication dependent on a genetically altered primer, we have used single cycle replication of murine leukemia virus (MLV)-derived vectors.…”
mentioning
confidence: 99%